2006
DOI: 10.1016/j.molcel.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of FGFR1 Kinase Is Mediated by a Sequential and Precisely Ordered Reaction

Abstract: Tyrosine phosphorylation of cellular proteins induced by extracellular cues serves as a critical mediator in the control of a great variety of cellular processes. Here, we describe an integrated experimental approach including rapid quench methodology and ESI-LC-MS/MS as well as time-resolved ESI-MS to demonstrate that tyrosine autophosphorylation of the catalytic tyrosine kinase domain of FGF-receptor-1 (FGFR1) is mediated by a sequential and precisely ordered reaction. We also demonstrate that the rate of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
203
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 28 publications
7
203
3
3
Order By: Relevance
“…It is noteworthy that the A-loop tyrosine in Eph RTKs is also a suboptimal phosphorylation site compared with juxtamembrane sites (13). Our data differ from the data on sequential phosphorylation of the FGFR1 kinase showing that phosphorylation on the A-loop Y653 is completed before the kinase insert and juxtamembrane sites are phosphorylated (20). This discrepancy could be because the FGFR1 kinase domain used by Furdui et al lacks the C-terminal Y766, the equivalent of Y769 in FGFR2.…”
Section: Order Of Transphosphorylation Reactionscontrasting
confidence: 92%
“…It is noteworthy that the A-loop tyrosine in Eph RTKs is also a suboptimal phosphorylation site compared with juxtamembrane sites (13). Our data differ from the data on sequential phosphorylation of the FGFR1 kinase showing that phosphorylation on the A-loop Y653 is completed before the kinase insert and juxtamembrane sites are phosphorylated (20). This discrepancy could be because the FGFR1 kinase domain used by Furdui et al lacks the C-terminal Y766, the equivalent of Y769 in FGFR2.…”
Section: Order Of Transphosphorylation Reactionscontrasting
confidence: 92%
“…Binding of FGF ligands to FGFRs induces dimerization and juxtaposition of the tyrosine kinase domains to initiate the sequential transphosphorylation of at least six tyrosine residues (Furdui et al 2006;Goetz and Mohammadi 2013;Ornitz and Itoh 2015). Activation of the FGFR tyrosine kinase domain allows the direct phosphorylation of the docked adaptor protein FGFR substrate 2α (FRS2α) and binding of other adaptor proteins, including phospholipase Cγ (PLCγ), signal transducer and activator of transcription 1 (STAT1), STAT3, and STAT5 (Ornitz and Itoh 2015).…”
Section: Fgf Signalingmentioning
confidence: 99%
“…Other phosphotyrosines serve as binding sites for recruitment and activation of downstream signaling molecules (Eswarakumar et al, 2005). It has recently been shown that tyrosines in FGFR1 are autophosphorylated in a sequential and strictly ordered manner (Furdui et al, 2006). In this way, the activated-FGFR transduces signals by activating different signaling cascades including Ras/mitogen-activated protein kinase (MAPK), PI3K/Akt, PLCg/PKC and p38 MAPK (Boilly et al, 2000).…”
Section: Introductionmentioning
confidence: 99%